2008
DOI: 10.1158/0008-5472.can-08-1643
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocyte Growth Factor Induces Gefitinib Resistance of Lung Adenocarcinoma with Epidermal Growth Factor Receptor–Activating Mutations

Abstract: Lung cancer with epidermal growth factor receptor (EGFR)-activating mutations responds favorably to the EGFR tyrosine kinase inhibitors gefitinib and erlotinib. However, 25% to 30% of patients with EGFR-activating mutations show intrinsic resistance, and the responders invariably acquire resistance to gefitinib. Here, we showed that hepatocyte growth factor (HGF), a ligand of MET oncoprotein, induces gefitinib resistance of lung adenocarcinoma cells with EGFR-activating mutations by restoring the phosphatidyli… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

20
505
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 558 publications
(527 citation statements)
references
References 39 publications
20
505
2
Order By: Relevance
“…First, target gene alteration, such as gatekeeper mutation or amplification of EGFR, and second, activation of bypass signaling, such as activation of HGF-MET signaling and the PIK3CA mutation (8,10,13,14). We have shown that the FGF2-FGFR1 autocrine loop is an alternative bypass track for acquired resistance to gefitinib in this study (Fig.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…First, target gene alteration, such as gatekeeper mutation or amplification of EGFR, and second, activation of bypass signaling, such as activation of HGF-MET signaling and the PIK3CA mutation (8,10,13,14). We have shown that the FGF2-FGFR1 autocrine loop is an alternative bypass track for acquired resistance to gefitinib in this study (Fig.…”
Section: Discussionmentioning
confidence: 62%
“…On the other hand, it is important to note that the phosphorylation status of EGFR itself was not affected by FGF2-FGFR1 activation and completely inhibited by gefitinib. Those were also observed in the cases of gefitinib resistance induced by the activation of HGF-MET signaling and considered to be common phenomena in the bypass track activation (10,14). Evaluating the status of EGFR phosphorylation before and after EGFR-TKI treatment may be essential to know whether the mechanism for resistance to EGFR-TKI is due to the activation of bypass track or not.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The fi rst study showing that HGF can induce gefi tinib resistance in lung adenocarcinomas with EGFR-activating mutations was that by Yano and colleagues ( 63 ), who found that HGF acts by restoring PI3K/AKT activation via phosphorylation of MET (but not of EGFR or HER3); moreover, they showed that strong immunoreactivity for HGF was detected in patients displaying primary or secondary resistance to gefi tinib. The same authors subsequently found that high HGF immunohistochemical reactivity was present in 29% of nonresponding patients, and that HGF expression was signifi cantly higher in tumors with acquired resistance than in sensitive ones ( 64 ).…”
Section: Non-small Cell Lung Cancermentioning
confidence: 99%
“…Although several possible mechanisms of secondary acquired EGFR mutations 11,12 or other unrelated pathways to EGFR genotypes 13 were reported, successful strategies for overc oming the resistance to EGFR-TKI have yet to be established . [14][15][16] Thus, the development of a novel and possible therapeutic strategy for patients with resistance to EGFR-TKI is an important clinical issue in medical oncology.…”
Section: Introductionmentioning
confidence: 99%